Novel Asymmetrical Linear Stapler (NALS) for pathologic evaluation of true resection margin tissue - Kang, Shin-Kwang; Bok, Jin San; Cho, Hyun Jin; Kang, Min-Woong (Journal of Thoracic Disease, 2018)
Background: The use of limited resection for lung cancer has increased with the accumulation of knowledge about early lung cancer. To decrease locoregional recurrence after a limited resection, it is important to confirm R0 resection at the true resection margin. In this study, we report a novel linear stapler that preserves the true resection margin tissue after organ resection. Methods: We used a Novel Asymmetrical Linear Stapler (NALS) made by Meditulip. On the resected organ side of NALS, there is a single row of titanium fasteners. To verify the utility of NALS and to compare its preservation of the resection margin tissue to a conventional stapler, we performed wedge resection of the lung in a porcine animal model and examined the pathology of the true resection margin. Results: Using NALS, we successfully divided and closed the lung tissues, as with the conventional stapler. There was no bleeding on either side or no air leakage from the remnant stapled tissue. The distance between the cutting edge and the titanium fasteners was 3.10 mm with NALS, which was sufficient to resect the true resection margin tissue for pathology evaluation. There was no squeezing artifact at the true resection margin on microscopic evaluation with NALS. With the conventional stapler, it is difficult to evaluate the pathology at the true resection margin due to the severe squeezing artifact. Conclusions: NALS preserves the true resection margin tissue and thus should be useful for evaluating the resection margin with a frozen section biopsy in oncology surgery.